Paip2 is localized to active promoters and loaded onto nascent mRNA in Drosophila - Kachaev, Zaur M. (Cell Cycle, 2018)
Paip2 (Poly(A)-binding protein – interacting protein 2) is a conserved metazoan-specific protein that has been implicated in regulating the translation and stability of mRNAs. However, we have found that Paip2 is not restricted to the cytoplasm but is also found in the nucleus in Drosophila embryos, salivary glands, testes, and tissue culture cells. Nuclear Paip2 is associated with chromatin, and in chromatin immunoprecipitation experiments it maps to the promoter regions of active genes. However, this chromatin association is indirect, as it is RNA-dependent. Thus, Paip2 is one more item in the growing list of translation factors that are recruited to mRNAs co-transcriptionally.